Testing the state of erythrocytes under hypertonic and posthypertonic shock - Чабаненко, О.О.; Єршова, Н.А.; Шпакова, Н.М. (46th Annual International Conference of Young Scientists "Cold in biology and medicine: current problems in cryobiology, transplantology, and biotechnology", Kharkiv, May, 25 2022, 2022)
To study the effect of the factors of erythrocytes cryodamage the model experiments were used. To investigate an impact on cells of damage factors acting at the freezing stage using hypertonic shock (HS), and the factors the action of those were realized at the thawing stage with posthypertonic shock (PHS). In the base of cell damage under action of temperature-osmotic shock there are the processes associated with transmembrane pores formation, therefore, the use of membranetropic substances is advisable. Research aim was to study the development of hypertonic and posthypertonic hemolysis of human erythrocytes at 37 and 0°C in the presence of chlorpromazine (CPR) and trifluoperazine (TFP). Hypertonic shock was performed by transferring erythrocytes into 4.00 mol/L NaCl, while posthypertonic shock was initiated by transferring the cells from dehydration medium (1.65 mol/L NaCl) to rehydration one (0.15 mol/L NaCl) at 37 and 0°C. The level of erythrocytes hemolysis was determined spectrophotometrically (λ = 543 nm). The erythrocytes are damaged under HS and PHS conditions. Hemolysis level of erythrocytes depends on temperature: at 0°C it was lower than at 37°C. The usage of CPR and TFP decrease of hypertonic hemolysis level of erythrocytes at temperatures 37 and 0°C, moreover antihemolytic (AH) activity of both amphiphilic compounds is about 2 times higher at 37°C. In contrast to the above, the efficacy of amphiphiles at PHS conditions of erythrocytes is observed only at 0°C. Comparative analysis of CPR and TFP efficiency showed higher AH activity of CPR (70%) compared to TFP (60%) under PHS conditions of erythrocytes, and, conversely, under HS conditions (0°C) the values of AH activity for TFP (80%) exceeded similar index of CPR (70%). But for both types of shock, the effective concentrations of CPR are higher than the ones for TFP. It was found that under HS conditions of erythrocytes the effective concentrations of amphiphiles were significantly lower compared to the values obtained under PHS conditions. The fact that to implement the protective effect of amphiphiles under PHS conditions of erythrocytes requires more substance may unlikely indicate the nature of hemolytic pores formation under action of the factors inherent to different stages of erythrocytes cryopreservation. Since the protective effect of amphiphiles is realized under PHS conditions only at low temperature and under HS conditions the compounds are more effective at 37°C than at 0°C, the mechanism of action of amphiphiles under HS conditions can be assumed to be associated with perturbation of erythrocyte membrane, while under PHS this can be due to its stabilization.
Chabanenko OO, Yershova NA, Shpakova NM. Testing the state of erythrocytes under hypertonic and posthypertonic shock In: 46th Annual International Conference of Young Scientists "Cold in biology and medicine: current problems in cryobiology, transplantology, and biotechnology", Kharkiv, May, 25 2022
Keywords: erythrocytes; amphiphilic compounds; hypertonic shock; posthypertonic shock